Modifikasi Pengolahan Minyak Kelapa Untuk Meningkatkan Kualitas Ampas Minyak Kelapa. Kajian Dari Konsentrasi Na-metabisulfit dan pemarutan. - Sukamto, Sukamto; Harmanto, Harmanto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2004)
The waste of coconut oil by dry processing have not be used, because that was not higienes. The objective of this research is to study effect of Na-metabisulfit concentration and sliecing waste quality. The method used in the research was Randimized Completed Block Design consisting Na-metabisulfit concentration rate (0, 750 and 1500 ppm) and sliecing (be slieced and was not slieced). The quality parameters evaluated in waste of cocnut were water conten, protein, free fatid acid, silfit residue, and organoleptic aspects including smell and colour. The statisical analiysis result indicated that sliecing were significant on water content, free fatid acid, and smell. Na-metabisulfit concentrations were significant on the protein, colour and smell. Key word : oil, coconut, Na-metabisulfit